Gap Score Analysis Indikator Transportation UI GreenMetric pada Perguruan Tinggi Vokasi: Studi Kasus Politeknik Negeri Medan - Nurkhasanah Rina Puspita; Soraya Muthma Innah Nasution; Veriza Agistin; Frans Tomy Syahputra Butarbutar (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Sustainable transportation is one of the key indicators in the UI GreenMetric ranking system, reflecting a university’s commitment to reducing carbon emissions and promoting sustainable campus development. This study aims to evaluate the achievement of the Transportation (TR) indicators in the UI GreenMetric at Politeknik Negeri Medan and identify improvement priorities based on the gap level for each indicator. A descriptive quantitative approach with a descriptive-evaluative method was employed. Data were collected through field surveys, observations of transportation facilities, vehicle counts, parking area measurements, and reviews of institutional documents and the UI GreenMetric 2025 assessment instrument. Data were analyzed using Gap Score Analysis, comparing actual scores with the maximum scores established by UI GreenMetric. The results revealed that Politeknik Negeri Medan achieved a Transportation score of 372.5 points, equivalent to 20.69% of the maximum score of 1,800 points. Campus mobility remains highly dependent on motorized vehicles, with a vehicle-to-population ratio of 0.18 and parking areas occupying 9.54% of the total campus area. Furthermore, the campus has not yet provided shuttle services, zero-emission vehicles, or information technology-based transportation systems. The Gap Score Analysis identified TR2 as the indicator with the highest gaps. Therefore, future transportation development should prioritize low-emission transportation modes, private vehicle reduction programs, and smart mobility implementation